Case report: Importance of early and continuous tocilizumab therapy in nephrotic syndrome associated with idiopathic multicentric Castleman disease: A case series - Kojima, Daiki; Yamaguchi, Shintaro; Hashiguchi, Akinori; Hayashi, Kaori; Uchiyama, Kiyotaka; Yoshimoto, Norifumi; Adachi, Keika; Nakayama, Takashin; Nishioka, Ken; Tajima, Takaya; Morimoto, Kohkichi; Yoshino, Jun; et al. (Frontiers in Medicine, 2023)
Idiopathic multicentric Castleman disease (iMCD) is a systemic and polyclonal lymphoproliferative disease involving multiple organs, including the kidneys, due to the overproduction of interleukin-6 (IL-6). Recently, several reports suggested that excessive IL-6 actions in iMCD have a causal relationship with the development of diverse histopathological renal manifestations which cause nephrotic syndrome. However, the treatment of such cases remains unclear. We report a series of three cases of nephrotic syndrome due to iMCD that helps to delineate the importance of early and continuous therapy with the anti-interleukin-6 receptor antibody tocilizumab. In the first, treatment was suspended for infectious control, and the patient presented with nephrotic syndrome due to diffuse mesangial and endocapillary hypercellularity without immune deposits complicating acute kidney injury. In the second, iMCD was treated with prednisolone alone. The patient suddenly developed nephrotic syndrome due to immune-complex glomerulonephritis, not otherwise specified, complicated with acute kidney injury. In the third, nephrotic syndrome secondary to membranous glomerulonephritis was diagnosed, with IgE antibodies to tocilizumab, and was therefore treated with prednisolone alone. In contrast to the first two cases, the third progressed to end-stage renal disease on hemodialysis. Taken together, this series suggests that clinicians should maintain clinical vigilance for iMCD as a possible underlying component of nephrotic syndrome, since iMCD presents with a variety of renal pathologies. Prompt initiation and continuous administration of tocilizumab are likely key determinants of renal outcomes in such cases. In particular, when tocilizumab is suspended due to infection or in the perioperative period, consideration of its expeditious resumption should be made, taking into account both the withdrawal period and systemic conditions.